Development of a multi-physic platform OLYMPE for magnet fusion design: Progresses update and applications. (July 2022) - Zani, L.; Bonne, F.; Bourcier, C.; Dejoie, F.; Hertout, P.; Hoa, C.; Lacroix, B.; Le Coz, Q.; Nunio, F.; Petit, V.; Torre, A.; Van Wambeke, C.; et al.
Highlights: The multiphysic platform OLYMPE development has progressed at CEA with lopps coupling TF design and various detailed analyses. EMD loop converges towards a consistent TF design with respect to magnetic field map. THD loop converges towards to a consistent TF design with respect to thermohydraulic performances. THDC loop converges towards to an optimized TF design with respect to overall magnet & cryoplant cost merits. MECD loop converges towards to a consistent TF design with respect to mechanical performances. Abstract: In the framework of tokamak design studies, the magnet system dimensioning stands as a crucial point, magnets being strong drivers for reactor performances. In this aim superconducting magnets design path to manufacture and integration should undergo several stages of development, including the detailed analysis for defined operation cases. Those studies are linked to several physic domains (electromagnetics, mechanics, thermohydraulics, thermal) that all show interdependances between each other. In this objective, the platform OLYMPE was developed at CEA, aiming at addressing those complex multi-physic problems in an integrated simulation tool, expected to improve the efficiency of the design workflow involving macroscopic and detailed analyses. The different OLYMPE submodules will be described and their dedicated simulation domain explained, together with the logic that led to the choice of specific modules interconnection. In fact several combinations of those modules are built in coupled mode so to ensure converging design loops. Their major role is to assess the refinement of magnet design at detailed scale in the objective to increase magnet design accuracy. Namely illustrating examples will be given with following loops: - TF system design coupled with thermohydraulics: it ensures the compliance of TF design with temperature margin criterion. - TF system design coupled with electromagnetics: it ensures the compliance of TF design with topologically-induced magnetic field map. - Overall TF design coupled with thermohydraulics and cryogenics: it ensures the optimization of TF design and its operation conditions with overall system merits (e.g. cost factor). - TF system design coupled with mechanics: it ensures the compliance of TF design with local stress criterion. The outcomes and methodological merits of these loops will be illustrated by applications on DEMO configurations, and performances cross-checks or comparisons with simpler models will also be provided to quantify the accuracy enhancement. Furthermore the management of the overall input database and the GUI interface will be presented in the aim of improving tool operability. Finally discussions on this emerging OLYMPE tool qualities will also be exposed, including calculation performances merits and further development perspectives.